TINDAK PIDANA PEMELIHARAAN SATWA INVASIF TANPA IZIN PADA KASUS IKAN ALIGATOR (Studi Putusan Pengadilan Negeri Malang Nomor 286/Pip.sus/2024/PN.Mlg) - Dwi Azizah, Moza Aprilya; Prawesthi, Wahyu; Damayanti, Sri Sukmana; Subekti, Subekti (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The phenomenon of keeping invasive species, particularly alligator gar (Atractosteus spatula), has become a serious issue in the protection of Indonesia's aquatic ecosystems. The presence of this predatory species not only threatens local biodiversity but also poses ecological risks that are difficult to reverse if released into their natural habitat. The urgency of this research lies in the weak implementation of regulations despite the clear prohibition on keeping these species as pets, as stipulated in Ministry of Marine Affairs and Fisheries Regulation No. 19 of 2020. This study aims to examine how the court interprets the elements of the criminal act of keeping invasive species through a case study of Malang District Court Decision No. 286/Pid.Sus/2024/PN.Mlg, as well as to answer the question of the extent to which the decision reflects the principle of ecological justice. The method used is normative legal research with a conceptual and case approach. Data was collected through a review of court decisions, laws and regulations, and related scientific literature. The analysis was conducted prescriptively to examine the fulfilment of the elements of the offence, the judges' considerations, and the implications of the decision for ecosystem protection. The results of the study show that the panel of judges found all elements of the crime to be proven, including the defendant's intent to keep alligator fish without official permission. The judges applied the principle of strict liability and the principle of precaution, but the sanctions imposed were relatively light compared to the threats in the law. The discussion shows that there is a gap between normative threats and sentencing practices, so that the deterrent effect has not been achieved. These findings also confirm that the anthropocentric paradigm is still dominant in Indonesian environmental law, while ecocentric values have not been fully adopted. The conclusion of this study emphasises the need for legal paradigm reform towards ecological justice, increased consistency in sentencing, and preventive strategies based on education and online trade monitoring. Further research is recommended to explore the consistency of similar verdicts in various regions and to quantify ecological losses